Financial fragility in developing countries: An analysis in the context of monetary policy and central bank independence - Bengü Tosun; Selim Başar (Journal of Central Banking Theory and Practice, 2024)
This study aims to examine the effects of monetary policies implemented by developed countries and central bank independence of developing countries on the financial fragility of developing countries. According to the findings, it was seen that the contractionary monetary policies implemented by the central banks of developed countries increase the financial fragility for both groups of countries, as do the change of central bank governors. However, the change in governors strengthens positive effects of contractionary monetary policies on the financial fragility.
Keywords: C33; E52; E58; F42; G00; 330; Financial Fragility; International Monetary Policy; Central Bank Independence; System GMM